2015
DOI: 10.1007/s12289-014-1209-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of relative tool position in accumulative double sided incremental forming using finite element analysis and model bias correction

Abstract: Double-Sided Incremental Forming (DSIF) uses two small, independently moving, hemispherical tools on either side of the sheet to form a desired shape by following a predefined tool path. This study was motivated by the observation that the relative tool position of the tools, specified in the tool path generation algorithm, affects the formed geometric accuracy. A methodology for defining the relative tool positioning in the tool path generation algorithm based on local part geometry is proposed using simplifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The prediction via the simplified model was very close to the experimental results in a certain range of angles and the deviation was controlled within 5 deg. The results show that the combination of the values of D and S is not unique when forming a specific wall angle [29,66]. A similar parametric study was also reported by Ren et al [28] as the tool gap and tool position angle were chosen as parameters.…”
Section: Deformationsupporting
confidence: 66%
See 3 more Smart Citations
“…The prediction via the simplified model was very close to the experimental results in a certain range of angles and the deviation was controlled within 5 deg. The results show that the combination of the values of D and S is not unique when forming a specific wall angle [29,66]. A similar parametric study was also reported by Ren et al [28] as the tool gap and tool position angle were chosen as parameters.…”
Section: Deformationsupporting
confidence: 66%
“…Toolpath optimization and combination with out-to-in DSIF toolpath are verified to be beneficial for the enhancement of formability and profile accuracy [47]. Other numerical analyses reveal the unique deformation mechanism in ADSIF of enhanced shearing and bending effect in contrast to dominant stretching and bending effect in conventional DSIF processes [7,29]. In summary, the ADSIF is a noteworthy strategy and has a considerable potential of applications.…”
Section: Toolpath Design In Dsifmentioning
confidence: 84%
See 2 more Smart Citations
“…compared with that in single point ISF. Smith et al[120] studied the deformation mechanism in ADSIF by numerical simulation and Ndip-Agbor et al[121] developed an effective strategy for relative tool position optimization in ADSIF. Moser et al[117] developed a new thickness correction model to compensate the tool path of the bottom tool.…”
mentioning
confidence: 99%